Gateway to modern mathematics adventures in iteration I - Shirali Sailesh A (Hyderabad Universities Press, 2009)
This book, which is at an elementary level, introduces the idea of iteration. It also explores various associated notions like fixed points, orbits, cycles, limit points, convergence, solution of equations and cobwebbing. It contains a large number of il
Keywords: Iterations(Mathematics); Iterative processes